Neutrophil-to-platelet ratio predicts mortality following percutaneous coronary intervention in patients with acute ST-elevation myocardial infarction - Lin, Yuhui; Dai, Wenjun; Chen, Yongquan; He, Xiaoqing; Xu, Yunhong (Frontiers in Physiology, 2022)
This study aimed to evaluate the value of neutrophil-to-platelet ratio (NPR) in predicting all-cause mortality in patients with ST-elevation myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI). We enrolled 186 patients with STEMI who underwent primary PCI in the Third Affiliated Hospital of Guangzhou Medical University between January 2017 and December 2018. Based on the NPR values, the patients were divided into two groups: the NPR > 0.035 group (n = 82) and the NPR ≤ 0.035 group (n = 104). All-cause mortality of the patients was followed up for 3 years. By the end of 3 years, 109 (58.6%) patients survived, 53 (28.5%) died, and 24 (12.9%) were lost to follow-up. Univariate analyses found that NPR was associated with all-cause mortality (P <0.05). In COX regression analyses, patients in the high NPR group had a higher risk of all-cause death than those in the low NPR group (HR = 2.296, 95% CI: 1.150 - 4.582). These results indicate that NPR could predict all-cause death in 3 years after primary PCI in patients STEMI. NPR values may be useful in risk stratification and in specifying individualized treatment in patients with STEMI. In addition, NPR is a low-cost and easily accessible indicator, if its strong predictive value is confirmed in further studies of other large populations, it can be introduced into clinical practice for effective application.